Cardiac arrhythmias and the athlete - Link, M. S.; Olshansky, B.; Estes, N. A. (Current opinion in cardiology, 1999)
Athletes, although the healthiest segment of society, can develop cardiac arrhythmias. Benign bradycardias and atrial and ventricular premature contractions are common and seldom require treatment. Supraventricular tachycardias are less common and are usually not life-threatening, but do require treatment. Ventricular arrhythmias, although uncommon, are life-threatening and require treatment. Most athletes with ventricular arrhythmias have structural cardiac abnormalities, and further competitive play is usually prohibited. Commotio cordis, which is a recently described syndrome of sudden death caused by low-energy chest wall impact, may account for a significant percentage of the sudden deaths in athletes.